الصفة المشبهة في معجم "المصباح المنير" للفيومي المقرئ: دراسة صرفية تحليلية - Hudassakinah binti Asha'ri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research approach The Likened Adjectives in Dictionary Written by Al-Fayumi Al-Muqri: Morphological and Analytical Study. It contains the study of structure of likened adjectives, focusing on the briefing of pattern and the sources of verb. This research used descriptive and analytical research method to discover the total numbers of likened adjectives which is used in this dictionary and describe the variety of each pattern in term of derived verbal and underived. The likened adjectives have been collected from that dictionary which is contain seven hundred and twelve (712) pages from two (2) volumes. The results indicated the number of pattern for the likened adjectives is thirty four (34). All the patterns is not interfered by female pattern which is mostly formulated based on the trilateral derived verb. They are trilateral underived then quadrilateral derived verb and the least one is quadrilateral underived verb. Although it seems most of the patterns of likened adjectives have their standardized feminine's structure, it should be surely the validity of the structures because some of them just used the male's structure similarly. In addition, the likened adjectives are mostly derived from trilateral verb then quadrilateral verb followed by quinquerilateral verb and the last one is derived from noun.